Analisis Faktor-Faktor yang Mempengaruhi Kecenderungan Kecurangan pada Pengelolaan Dana Desa (Survei pada Pemerintahan Desa di Kabupaten Bandung Barat) - Dea Rosifa; Iyeh Supriatna (Indonesian Accounting Research Journal, 2022)
This study aims to determine the factors that affect the tendency of Village Fund management fraud in West Bandung District with the Fraud Hexagon Theory perspective. This study uses a quantitative method with the population is the village apparatus in West Bandung District and has 95 samples from 22 village governments that were selected by purposive sampling technique. The hypothesis is tested using a Partial Least Square (PLS) based approach that is carried out by the Smart PLS 3.0 application. The results showed that Stimulus (Compensation Suitability) no significantly negatively affects the tendency of Village Fund management fraud. In contrast, Collusion significantly negatively affects the tendency of Village Fund management fraud. Then, Capability (Village Apparatus Competence) and Rationalization (Organizational Culture) significantly positively affect the tendency of Village Funds management fraud. However, Opportunity (Effectiveness of Government Internal Control System) and Ego (Village Apparatus Morality) no significantly positively affect the tendency of Village Fund management fraud.